Kenyan farmers turn to grain amaranth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Grain amaranth (Amaranthus hybridus) offers the prospect of substantially increasing food output in dryland areas of Kenya, according to a local NGO, Strategic Poverty Alleviation Systems (SPAS)...